Diversitas Serangga yang Berasosiasi dengan Tanaman Jeruk Pamelo (Citrus maxima) : The Diversity of Insect Assemblages on Pummelo (Citrus maxima) - Ria Anisa, Henta; Atmowidi, Tri; Priawandiputra, Windra; Kahono, Sih (Jurnal Sumberdaya Hayati, 2022)
Pummelo (Citrus maxima) is a species that has a high economic value and several cultivars are found in Indonesia. These plants interact with many species of insects, either as predators, parasitoids, or pollinators. This study aimed to measure the diversity of insects associated with pummelo and its environmental factors. Observation of insect diversity used scan sampling method in thirty plants on sunny days. Results showed that a totally of 1,388 individual insects belonging to 17 species in 11 families and 5 orders were found, i.e., Hemiptera, Orthoptera, Coleoptera, Hymenoptera, and Lepidoptera. The dominant insect species found were Camponotus sp. (Hymenoptera: Formicidae), Tetragonula laeviceps (Hymenoptera: Apidae), and Chrysolina sp. (Coleoptera: Chrysomelidae). The number of individual insects was high in the morning (07.00-08.00), while the number of species was high in the noon.